SPATIAL AND TEMPORAL VARIABILITY OF 40 YEARS TEMPERATURE AND PRECIPITATION IN THE SAVANNA REGION, NIGERIA - Muhammed, Ismail; Abdussalam, Auwal F.; Isa, Zaharaddeen (FUDMA JOURNAL OF SCIENCES, 2023)
The fact that climate is varying globally and across regions and within drainage basins are no longer disputable, the causes of these variability have been attributed to natural and anthropogenic (human activities on the earth) factors, In the last four decades, the anthropogenic factors have become more dominant. Temperature and precipitation record in the savanna region for 40 years of six synoptic weather stations were obtained from Nigerian Meteorological Agency (Nimet). The obtained data covered two stations from each vegetation zone namely; Sahel Savanna (Maiduguri and Sokoto), Sudan Savanna (Katsina and Kano) and Guinea Savanna (Kaduna and Niger). Coefficient of variance (CV), mean, standard deviation kurtosis and skewness were used to assess the inter annual variability across the savanna regions. The result obtained from the analysis revealed that, there is moderate variability of Precipitation in the Guinea, Sudan and Sahel savanna and low variability in temperature in the whole of savanna region.